Unveiling the conserved nature of Heliconia chloroplast genomes: insights from the assembly and analysis of four complete chloroplast genomes - Cheng, Xin; Shi, Chengcheng; Yang, Ting; Ge, Qijin; Kress, W. John; Liu, Xin (Frontiers in Plant Science, 2025)
IntroductionHeliconia, a genus within the Zingiberales order, is renowned for its diverse morphology, suggesting a rich genetic reservoir. However, genetic research on plants within the Heliconiaceae family has primarily focused on taxonomy and phylogenetics, with limited exploration into other genetic aspects, particularly the chloroplast genome. Given the significance of chloroplast genomes in evolutionary studies, a deeper understanding of their structure and diversity within Heliconia is essential.MethodsIn this study, we sequenced and assembled the complete chloroplast genomes of four representative Heliconia species: Heliconia bihai, Heliconia caribaea, Heliconia orthotricha, and Heliconia tortuosa. The chloroplast genomes were analyzed for structure, gene content, and nucleotide diversity. We also performed comparative analysis with other species within the Zingiberales order to investigate structural and functional differences.ResultsThe assembled chloroplast genomes of the four Heliconia species exhibited a typical quadripartite structure and ranged in length from 161,680 bp to 161,913 bp. All genomes contained 86 protein-coding genes. Comparative analysis revealed that the chloroplast genome structures of the different Heliconia species were highly conserved, with minor variations. Notably, the chloroplast genome of Heliconia was slightly shorter than those of other Zingiberales species, primarily due to the reduced length of the inverted repeat region. In terms of nucleotide diversity, Heliconia species exhibited lower diversity in their chloroplast genomes compared to other families within the Zingiberales order.DiscussionThis study provides valuable insights into the conserved nature of the chloroplast genome in Heliconia. The reduced chloroplast genome size, particularly the shortened inverted repeat region, marks a distinct feature of Heliconia within the Zingiberales family. Our findings also underscore the low nucleotide diversity within the chloroplast genomes of Heliconia species, which could be indicative of their evolutionary history and limited genetic differentiation. These results contribute to a broader understanding of chloroplast genome evolution in the Zingiberales and offer important genetic resources for future research on Heliconia and related species.